International perspectives on research in early childhood education - Spodek, Bernard; Saracho, Olivia N. (Contemporary perspectives in early childhood education., 2005)
In the chapters that follow, the history and current status of early childhood education in selected countries, along with a review of current research that is being conducted in these countries will be presented. In essence this will provide a glimpse of the intellectual base of early childhood education in many parts of the world.